Business strategies and management for sustainability - Laszlo, Christopher (Berkshire essentials., 2013)
This book explores how a green economy can be created and sustained using sustainability in both the environmental and financial sense. It covers topics such as green gross domestic product, greenwashing, risk management, and local living economies that strive to operate using accountable practices. The book emphasizes social responsibility (CSR), and assesses the ways in which we can make a measurable difference in how business is conducted.